DIGITAL MARKETING CHANGES OF MICRO-SMALL ENTERPRISES BEFORE AND DURING COVID-19 PANDEMIC IN BOGOR, INDONESIA - Alfa Chasanah; Siti Jahroh; Febriantina Dewi (School of Business, IPB University (SB-IPB), 2021)
The advance of information technology has opened up the digital marketing which spreads and is adopted fast. Micro-small Enterprises (MSEs) has also adopted this technology, especially during the Covid-19 pandemic due to the restricted movement policy. This paper aims to analyze digital marketing used by MSEs during this Covid-19 pandemic in Bogor, Indonesia. Specifically, the objectives are (1) to identify digital marketing used by MSEs before and during Covid-19 pandemic, and (2) to analyze the obstacles and challenges in utilizing digital marketing by MSEs in Bogor, Indonesia. Questionnaire survey was conducted online to MSEs in Bogor in August-September 2020 with 27 respondents filled up the form. The respondents of MSEs in this study realized the importance of digital marketing, which the majority has already utilized, and its use has even increased during the pandemic. The results of this study showed that firstly, the majority of MSEs utilized social media and WhatsApp group as their digital marketing before and during the pandemic, in which around 11 percent of respondents started to utilize digital marketing to increase their sales during the pandemic. Secondly, the respondents were aware of their limited time and skills in presenting good content marketing in their social media. However, they realized digital marketing offers an opportunity to expand their market. Keywords: content marketing, information technology, social media, WhatsApp group